Working Paper 53: Good governance and the just transition: Implications for renewable energy companies (Basel Institute on Governance Working Papers, 2024)
There is broad agreement that ensuring a just energy transition is key for achieving the trust and support from citizens needed to succeed with the green transition and the COP28 goal of tripling renewable energy capacity by 2030.This paper discusses the concept of a just transition, with a particular focus on the importance of achieving a transition that benefits both local communities and society at large. It examines the governance and corruption challenges that could jeopardise this goal and discusses how industry associations and companies in the renewable energy sector could step up its efforts to address these challenges to realise the ambition of a just transition.The paper draws on lessons from the experience of tackling governance and corruption risks in the extractive sector and sets out proposals on how to accelerate collective action in the renewable energy sector. About this reportThis is a guest Working Paper of the Basel Institute on Governance, ISSN: 2624-9650. You may share or republish the report under a Creative Commons CC BY-NC-ND 4.0 licence. The contents are the sole responsibility of the authors and do not necessarily reflect the official position of the Basel Institute on Governance, University of Basel or funding organisations.Suggested citation: de Vibe, Maja, and Mark Robinson. 2024. ‘Good governance and the just transition: Implications for renewable energy companies.’ Working Paper 53, Basel Institute on Governance. Available at: baselgovernance.org/publications/wp-53.
Keywords: Collective Action; Green Corruption; Energy transition; Private Sector; Climate change; Net zero